ANTHROPOMETRIC MEASUREMENT OF METABOLIC AGE USING NECK CIRCUMFERENCE - Ni Nyoman Sri Yuliani; Elsa Trinovita (Poltekkes Kemenkes Semarang, 2020)
Excessive fat accumulation in the obese body causes chronic low-grade inflammation. The continuous occurrence will affect health, which may lead to damage to cell metabolism related to metabolic age. Therefore, anthropometric application by measuring neck circumference (NC) and body mass index (BMI) was performed. The aim of this study was to determine NC cut-off which can be used to identify the increase of metabolic age in an individual. This study is a diagnostic study using cross sectional design using subjects who met the criteria needed for this study (n = 82). BMI and NC anthropometric measurements were performed in this study. Metabolic age was measured using Bioelectrical Impedance Analyzer (BIA). Data were analyzed using 2 x 2 diagnostic table and Receiver Operating Characteristic (ROC) curve to obtain Area Under Curve (AUC). The results showed that the highest BMI was obese (65.8%) with the most common age of 30-57 years old. The result of ROC-AUC NC on metabolic age showed that AUC value of NC measurement was 0.77, cut-off ≥ 33 cm, sensitivity 71.2%, and specificity 69.6%. This study concludes that the cut-off value of NC in predicting the increase of metabolic age had good sensitivity and specificity.